Improving Educational Outcomes by Providing Educational Services through Mobile Technology - El-Sofany, Hosam Farouk; El-Seoud, Samir A.; Al-Turki, Turky; El-Howimel, Hasan; Al-Sadoon, Amjad (International Journal of Interactive Mobile Technologies (iJIM), 2013)
The use of Computers, Networks, and Internet has successfully enabled educational institutions to provide their students and instructors with various online educational services. With the recent developments in M-learning and mobile technology, further possibilities are emerging to provide such services through mobile devices such as mobile phones and PDAs. By providing the educational services using wireless and mobile technologies, the educational institutions can potentially bring great convenience to those off-campus students who do not always have time to find Internet enabled computers to get the important educational information from their academic institutions. With the mobile or M-educational services, both the students and the instructors can access the services anytime and anywhere they want. This paper discusses those M-educational services that can be moved to the mobile platform and then presents the system prototype and architecture that integrate these services into the mobile technology platform. The paper will conclude with a description of the formative evaluation of the system prototype.